Perceived Usefulness and Perceived Ease of Use of Online Learning for Islamic Religious Education Teacher - Hariman Surya Siregar (Jurnal Pendidikan Islam, 2023)
The primary objective of this study is to examine how the perceived ease of use and usefulness of online learning, specifically using the SPACE (Sistem Pembelajaran Agama Cara Elektronik/Electronic Way of Religion Learning System) platform, impact the effectiveness of teaching professional education students. The study employs a mixed-methods approach, combining both qualitative and quantitative methods, and utilizes descriptive techniques. The research instruments utilized include interview forms and the TAM (technology acceptance model) questionnaire, which assess the participants' perceptions of the ease of use and usefulness of online learning. The research sample was selected using purposive sampling. Data analysis involved the utilization of multiple linear regression analysis. The findings of the study indicate a notable and significant influence of the perceived ease of use and usefulness of online learning. This is supported by the observation that the graduation rate of professional education students who acquire teacher professional certificates increased by 14.77% as a result.